2015
DOI: 10.1016/j.immuni.2015.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Mutations in the Autoimmune Regulator AIRE Are Associated with Common Organ-Specific Autoimmune Diseases

Abstract: The autoimmune regulator (AIRE) gene is crucial for establishing central immunological tolerance and preventing autoimmunity. Mutations in AIRE cause a rare autosomal-recessive disease, autoimmune polyendocrine syndrome type 1 (APS-1), distinguished by multi-organ autoimmunity. We have identified multiple cases and families with mono-allelic mutations in the first plant homeodomain (PHD1) zinc finger of AIRE that followed dominant inheritance, typically characterized by later onset, milder phenotypes, and redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
230
3
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 241 publications
(244 citation statements)
references
References 47 publications
9
230
3
2
Order By: Relevance
“…Mutated AIRE protein with point mutations in the HSR domain (L28P, L29P, W78R, and L93R) are distributed throughout the cytoplasm with some presence in the nucleus but not found in the concentrated specks as WT-AIRE, which is consistent with HSR domain mutations causing drastic decreases in INS-VNTR activation. Our study showed cytoplasm distribution of L28P AIRE in clusters and was not as apparent as previously reported as totally diffuse in the cytoplasm and nucleus (31,32). The discrepancy could be due to the cell type difference and/or fluorescencetagged fusion L28P (7).…”
Section: Mutation In Different Functional Domains Interferes With Airsupporting
confidence: 60%
See 1 more Smart Citation
“…Mutated AIRE protein with point mutations in the HSR domain (L28P, L29P, W78R, and L93R) are distributed throughout the cytoplasm with some presence in the nucleus but not found in the concentrated specks as WT-AIRE, which is consistent with HSR domain mutations causing drastic decreases in INS-VNTR activation. Our study showed cytoplasm distribution of L28P AIRE in clusters and was not as apparent as previously reported as totally diffuse in the cytoplasm and nucleus (31,32). The discrepancy could be due to the cell type difference and/or fluorescencetagged fusion L28P (7).…”
Section: Mutation In Different Functional Domains Interferes With Airsupporting
confidence: 60%
“…An animal study using a G228W knock-in mouse model has shown that this variant acted in a dominant negative manner to cause a unique autoimmune syndrome (34). A recent report has identified multiple cases and families with non-allelic mutations in AIRE with dominant inheritance (31). They studied the AIRE dominant negative mutations in the PHD1 domain of APS-1 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Elles se caractérisent par une divergence des profils auto-immuns retrouvés chez les patients. Ainsi, lorsque la mutation est hétérozygote, les patients présentent un retard dans l'apparition des signes cliniques caractéristiques du syndrome et une pénétrance incomplète [31]. Si les mutations dans le gène Aire sont associées à des profils d'auto-immunité, il apparaît aussi qu'en l'absence de mutations identifiées, une faible expression de la protéine soit également associée à des perturbations du système immunitaire.…”
Section: Liens Entre Faible Expression De Aire Et Auto-immunitéunclassified
“…APS-1 is a rare, recessive monogenic disease that is caused by mutations in the autoimmune regulator (AIRE) gene, characterised by the presence of two of the three main components: PAI, hypoparathyroidism and chronic mucocutaneous candidiasis, which has been reviewed elsewhere (20). Recently, several monoallelic mutations in AIRE's PHD1-domain were found to be associated with a milder form of APS-1 masquerading sometimes as APS-2, often with vitiligo and pernicious anaemia as disease components (21). Isolated PAI and APS-2 share the same…”
Section: Incidence and Prevalencementioning
confidence: 99%